ChemInform Abstract: Palladium‐Catalyzed Intramolecular Oxidative Heck Cyclization and Its Application Toward a Synthesis of (.+‐.)‐β‐Cuparenone Derivatives Supported by Computational Studies. Issue 33 (25th July 2013) - Ray, Devalina; Nasima, Yasmin; Sajal, Mal K.; Ray, Priyanka; Urinda, Sharmistha; Anoop, Anakuthil; Ray, Jayanta K.
Abstract The novel methodology, applied to various homoallylic alcohols, leads to formation of cyclopentenone structures and is thus suitable in the synthesis of sesquiterterpene molecules.